2008
DOI: 10.1105/tpc.107.057752
|View full text |Cite
|
Sign up to set email alerts
|

Potential Sites of Bioactive Gibberellin Production during Reproductive Growth inArabidopsis 

Abstract: Gibberellin 3-oxidase (GA3ox) catalyzes the final step in the synthesis of bioactive gibberellins (GAs). We examined the expression patterns of all four GA3ox genes in Arabidopsis thaliana by promoter–β-glucuronidase gene fusions and by quantitative RT-PCR and defined their physiological roles by characterizing single, double, and triple mutants. In developing flowers, GA3ox genes are only expressed in stamen filaments, anthers, and flower receptacles. Mutant plants that lack both GA3ox1 and GA3ox3 functions d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
218
0
13

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 227 publications
(252 citation statements)
references
References 51 publications
21
218
0
13
Order By: Relevance
“…2c-e), where the sporopollenin material is produced for the outer wall development [9][10][11][21][22][23] . Considering that GAMYBs, CYP703As and GA biosynthesis genes in flowering plants are also co-expressed in the tapetal cells and microspores 1,8,12,[24][25][26] , these observations indicate that SmGAMYB activity in these tissues of Selaginella is required to mediate GA signalling during the outer wall formation of microspores.…”
Section: Molecular Characterization Of Smgamyb and Ppgamybsmentioning
confidence: 82%
“…2c-e), where the sporopollenin material is produced for the outer wall development [9][10][11][21][22][23] . Considering that GAMYBs, CYP703As and GA biosynthesis genes in flowering plants are also co-expressed in the tapetal cells and microspores 1,8,12,[24][25][26] , these observations indicate that SmGAMYB activity in these tissues of Selaginella is required to mediate GA signalling during the outer wall formation of microspores.…”
Section: Molecular Characterization Of Smgamyb and Ppgamybsmentioning
confidence: 82%
“…S1). Previous studies have shown that the vegetative tissues of Arabidopsis and the fern S. moellendorffii contain approximately 1 ng g 21 dry weight (Hu et al, 2008) and 1 ng g 21 fresh weight GA 4 , respectively (Hirano et al, 2007). From LC-MS/MS measurement, GA 4 is presumably not present in P. patens, but if it is the amount must be less than 1.5 pg g 21 fresh weight (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…44 GA-deficient mutants in Arabidopsis and tomato showed abnormal stamen development, 45,46,47 while extreme GA deficiency revealed female sterility. 48,49 No viable pollen develops in severe GA-deficient mutants, and sepals, petals, and pistils are underdeveloped, leading in some cases even to premature abortion of the flower.…”
Section: Ga In the Flowering And Sex Expressionmentioning
confidence: 99%